Laser transmission welding of polymers – A review on process fundamentals, material attributes, weldability, and welding techniques. (December 2020) - Acherjee, Bappa
Highlights: An extensive review is provided on several aspects of the laser transmission welding (LTW) process. The process fundamentals, specifications, and requirements of the LTW process are addressed. The effects of compositions and the condition of polymers on the performance of the welds are reviewed. The laser weldability of polymers is discussed by considering polymer compatibility issues. Different laser transmission welding techniques and application strategies are evaluated. Abstract: Laser technology often offers solutions where existing technologies have struggled or require improvements. Over the last two decades, laser transmission welding (LTW) has become a viable fabrication method for industries that engaged in polymer welding. This paper presents a comprehensive review on several aspects of LTW process. In specific, this review focuses on four major aspects of the LTW: (a) process fundamentals, including operating principles and process requirements; (b) compositions and pre-welding conditions of polymers and their effects; (c) laser weldability of polymers, considering compatibility and non-compatibility issues; and (d) welding techniques and application strategies, including technological variants and the transformation of application strategies from absorber-based to absorber-free laser welding of polymers. The conclusion of the review and the prospects for further research work are eventually addressed.